The Book of Genesis in Late Antiquity Encounters Between Jewish and Christian Exegesis - Grypeou, Emmanouela; Spurling, Helen (Leiden : BRILL, 2013)
This volume examines the relationship between rabbinic and Christian exegetical writings on the book of Genesis in the Eastern Roman Empire and Mesopotamia, and illuminates the history of relations between Jews and Christians in Late Antiquity.
Description based upon print version of record.
Keywords: Bible. O.T. Genesis -- Criticism, interpretation, etc. -- History -- Early church, ca. 30-600.; Bible. -- Criticism, interpretation, etc. -- History -- Early church, ca. 30-600.; RELIGION / Biblical Studies / Old Testament; Electronic books